Prevalence of exclusive breastfeeding and factors related to early weaning in a Child-Friendly Hospital (Research, Society and Development, 2021)
The objective was to estimate the prevalence of exclusive breastfeeding in children living in the municipality of Santa Cruz - RN and to identify the factors associated with early weaning. A longitudinal study, of a quantitative character, carried out from April / 2019 to November / 2020, aimed at mothers and their respective children born in a Baby-Friendly Hospital. A total of 152 children / mothers were followed up through monthly home visits. For data collection, a structured questionnaire was used containing variables related to socioeconomic data, breastfeeding, pregnancy and childbirth. The collected data were organized in the Epidata (version 3.1) and Excel (version 2010) programs. For the analysis, the STATA program (version 10.0) was used. The introduction of other milks started in the 1st month in 1.3% of the children. The main reasons reported by mothers for early weaning were insufficient milk (16.6%) and rejection by the baby (16.6%). In the 6th month, the prevalence of EBF was only 8.6%, while 60.5% performed complementary breastfeeding. Early weaning was associated with maternal age (p = 0.035), type of delivery (p = 0.003), and difficulty in sucking milk (p = 0.022). This work is pioneering in the region, the knowledge obtained in this study can contribute to the implementation of programs and the adoption of measures aimed at stimulating the practice of EB.